Regime Shifts in Microbial and Water Quality Dynamics in Red Tilapia Ponds - Ziyan Liu; Jiaqi Li; Lei Luo; Yang Yu; Jianing Yan; Caiyun Sun; Xiangjun Miao; Wensheng Li (Microorganisms, 2025)
Changes in the aquatic ecological environment have a significant impact on aquaculture efficiency. In order to understand the changes in water quality and the dynamics of microalgae and bacteria in the process of aquaculture, 16S rRNA and 18S rRNA high-throughput sequencing technologies were used to determine the microorganisms in a red tilapia (Oreochromis sp.) aquaculture pond. During the breeding period (from 6 July 2023 to 13 November 2023), water samples were collected from three ponds, on average once every 20 days. The results of water quality analysis showed that at the end of culture (13 November 2023), the concentrations of NH4+-N and NO2−-N increased significantly, and both the air temperature (36.00 ± 0.00 to 21 ± 0.00 °C) and water temperature (32.83 ± 0.29 to 22.75 ± 0.42 °C) decreased significantly. The NH4+-N and NO2−-N concentrations increased by 597% (0.67 ± 0.17 to 4.67 ± 0.33 mg/L) and 782% (0.34 ± 0.16 to 3.00 ± 1.15 mg/L), respectively, from T1 to T6. Bacterial diversity decreased to T3 and then increased. The relative abundance of hgcI_clade (from 14.91% to 7.18%) and CL500-29_marine_group (from 3.35% to 1.39%) in aquaculture water generally decreased with the extension of aquaculture time. The abundance of Komma increased from T1 (1.44%) to T3 (13.90%) and decreased from T3 to T6 (4.21%). The pH, dissolved oxygen concentration, and temperature were main factors affecting the dynamics of bacteria, while dissolved oxygen, NH4+-N, and NO2−-N concentrations affected that of microalgae. In conclusion, this study revealed regime shift in the water quality and microalgal–bacterial community with increasing culture time in red tilapia aquaculture ponds.